2016
DOI: 10.1016/j.ijplas.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of thermal and mechanical behavior of a magnesium alloy AZ31 during electrically-assisted micro-tension

Abstract: Many researchers have used a material response function termed ''electroplasticity'' to account for the mechanical behavior of metals subjected to electric current during plastic deformation. However, other researchers claimed that the electrically-assisted (EA) deformation behavior of metals could be successfully characterized using thermal-mechanical constitutive models without the need for electroplasticity theories. In order to examine the controversial mechanisms and determine which dominates the flow str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…They found the current density threshold to achieve an effective thermal softening for each metallic alloy. Previously, they also published electrically-assisted micro-tension results to describe the thermomechanical behaviour of the AZ31 magnesium alloy under different current densities and, consequently, different joule effects [17]. As a result, the thermal softening was attributed only to the contribution of the joule effect and the change of the material resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…They found the current density threshold to achieve an effective thermal softening for each metallic alloy. Previously, they also published electrically-assisted micro-tension results to describe the thermomechanical behaviour of the AZ31 magnesium alloy under different current densities and, consequently, different joule effects [17]. As a result, the thermal softening was attributed only to the contribution of the joule effect and the change of the material resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…rather than before the high-rate heating stage (i.e., within 1 s after turning on electricity and showing very high Joule heating rate) [14] for all the tests to avoid some additional effects on the mechanical behavior of AZ31 sheets such as thermal expansion. Also, it should be mentioned that all the tests were performed under a strain rate of 0.01 s -1 until fracture and run at least 3 times for repeatability.…”
Section: Tensile Testsmentioning
confidence: 99%
“…It was found that the electrically-induced temperature was non-uniformly distributed in the gauge area with the maximum temperature occurring at the center of specimens due to the symmetric configuration of uniaxial tension [14,15]. The maximum temperatures during EA tension were averaged for samples with various grain sizes and specimen sizes, which were plotted against the square of current density.…”
Section: Joule Heating Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…(3) analysis of machine performance under mechanical loading; (4) design of machine electrical setting path and insulation; (5) multi-pass process analysis; (6) design of power transmission system (axial/radial/torque feeding mechanisms), roll bearing system, cooling system, workpiece feeding mechanism, and other related mechanical connection support components; (7) design and optimization of roll profiles/dimensions; (8) analysis and simulation of the rolling process; (9) development of engineering drawings and fabrication; (10) assembly and calibration of the EA tube rolling machine; (11) design and integration of the electrical control system; (12) hardware integration for high power supply electrically-assisted rolling process; (13) induction heating system integration; (14) experimental tests for the new rolling process. Through the process from conceptual design to final machine calibration and experimental tests, there are many technical and physical works that have been implemented and improved for the best performance of the innovative prototype.…”
mentioning
confidence: 99%